KARAKTERISTIK MASJID JAMI’ BANJARMASIN - Ilhami, Hamidi (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2018)
The architectural system cannot be separated from the environmental system, even both have very close reciprocal relationships. Therefore, the shape of a building is a creation of human culture to adopt and adapt to its environment, whereas an environment will greatly affect the shape of the building made by the local community to meet their needs. The characteristics of buildings are a record of how environment, culture, and other things influence the buildings. 'Jami Mosque' of Banjarmasin is one of the buildings. Its presence in the beach environment made it adopt the tradition of a stilt building. This building, however, shows very distinctive characteristics. One the one hand, the original characteristics of the ancient Nusantara mosque is still maintained, but the influence from outside and local are also obvious. By using morphological analysis and building style, cultural processes occurred in the circumstances could be easily understood. The architectural characters and decorations has created some peculiarities.